Fruit drop: I. Specific characteristics and varietal properties of fruit drop - Racskó, J.; Nagy, J.; Soltész, M.; Nyéki, J.; Szabó, Z. (International Journal of Horticultural Science, 2006)
The basic conditions of fruit set (synchronic bloom, transfer of pollen, etc.) still do decide definitely the fate of the flower in spite of the best weather conditions. Beyond a set quantity of fruits, the tree is unable to bring up larger load. A system of autoregulation works in the background and causes the drop of a fraction of fruits in spite of the accomplished fertilisation and the equality of physiological precedents. This study discuss this physiological process based on the international specific literature. The further development of fruits maintained on the tree depends mainly on the growing conditions (e.g. water, supply of nutrients, weather adversities, pruning, fruit thinning, biotic damages, etc.), which may cause on their own turn fruit drop especially at the time of approaching maturity.